Art and the Writing of Sacred Words (Al-Qamar, 2021)
This article is intended to define the artistic caliber of three calligraphists in Pakistan, Arif Khan, Tahir Mughal (Bin Qullander) and Shiblee Muneer. Their devotion to the sacred words of Holy Quran and their ability to combine the two genres; the art of painting and the art of writing (calligraphy), very lucratively and that make them exceptional. They believe the shape of letters and words from the Holy Quran are divinely intended and ordained and its elaboration in the form of calligraphic expressions endowed by the artistic language would be adequate to bring a believer into contact with the divine power. The rhythm of the calligraphy, symbolic use of forms and vibrant colors, the flow of the writing script moving from right to left side, reflect the great aesthetic sense of these calligraphists which is similar to the beauty that is known to the western world as modern abstract art.
Keywords: Art of Calligraphy; Contemporary Art; Art from Pakistan; Painterly Calligraphy; Sacred Art; symbolic calligraphy